Height control for small periodic structures using x-ray radiography - Schuettler, M.; Meyer, Pascal Edouard; Schaff, Florian; Yaroshenko, A.; Kunka, Danays; Besser, H.; Pfeiffer, F.; Mohr, J. (Measurement Science and Technology, 2016)
We report on a method to characterize the height of periodic x-ray absorbing structures. Such structures are used for example in grating-based x-ray interferometry. In contrast to other techniques, our approach allows for a non-destructive determination of the height based on a few transmission measurements. It can be used with conventional laboratory-based x-ray setups and is therefore of great interest at the application sites of the structures, as it allows further characterization without the need of additional hardware. Here we present the principle of the method, show first results acquired with an absorption grating and compare them with theoretical calculations and those obtained using a destructive method.
CRIS-Team Scopus Importer:2023-03-08
Keywords: height measurement; medical imaging; microstructures; phase-contrast; radiography; x-ray gratings